Effect of Chronic Administration of Justicia secunda Vahl in Mice Diabetized with Streptozotocin - Tomás Fregoso-Aguilar; Perla Xóchitl Escamilla-Ramírez; Dulce E. Nicolás-Álvarez; Jorge Alberto Mendoza-Pérez; Eduardo Osiris Madrigal-Santillán; Judith Margarita Tirado-Lule; Elda Victoria Rodríguez-Negrete; Eduardo Madrigal-Bujaidar; Isela Álvarez-González; Gabriela Ibáñez-Cervantes; Ángel Morales-González; José A. Morales-Gonzalez (Diabetology)
Certain pharmacological properties of the methanolic extract of Justicia secunda Vahl leaves (Acanthaceae) were evaluated in Streptozotocin (STZ)-treated albino mice to confirm whether it could be considered an alternative candidate for the treatment of diabetes. Using qualitative phytochemistry, alkaloids, flavonoids, and tannins were detected. In an in vitro DPPH antioxidant activity test, high extract concentrations inhibited the radical by 90% during the first minutes of the reaction. The extract presented a slight genoprotective effect on mouse peripheral blood during the last days of the micronucleus test. Oral administration of the extract at a high dose every two days for 6 weeks caused a hypoglycemic effect in STZ-treated mice, protection against weight loss, and decreased blood triglyceride levels from week 3 of treatment. These effects could be mediated by the antioxidant activity of the detected metabolites and, perhaps, by an inhibitory effect on intestinal α-glucosidase. This renders J. secunda a good candidate for the long-term alternative treatment of diabetes without abandoning allopathic therapy.